Science, Mathematics, ICT, and Engineering (SMIE) educators’ strategies to contribute to the SDG No. 9 in Industry, Innovation and Infrastructure through the learning processes - Ram Eujohn J. Diamante; Bernie S. Bayogos; Jonathan Solano; Billy Joe C. Lupera; Daphne Shane C. Clarin; Kim Jay C. Encio (Environment and Social Psychology, 2025)
As learning across the world becomes more leaning in sustainability as its focus, it is crucial that educational instructions that are delivered in practice are aligned with the Global Sustainable Development Goal 9, which is Industry, Innovation, and Infrastructure. The current literature underscores the role of SMIE education in local development. However, there is still no practical or empirical evidence from these studies on how educators in practice incorporate SDG 9 principles and therefore foster the development of students' creativity, critical thinking, and problem-solving skills. This research used an exploratory qualitative approach with 18 teachers from public schools in Iloilo Province, Philippines, who were purposively chosen. These teachers were from the fields of Science, Mathematics, ICT, and Engineering. The study applied reflexive thematic analysis to reveal the connections among teaching methods, curriculum integration, and students' competencies and skills. The findings emphasize teacher-led strategies such as project-based learning, solving real-world problems, using technology, and collaborating across disciplines that not only prepare students for the challenges of sustainable industry and resilient infrastructure but also enhance their skills. In addition, some limitations of the study were the selection of public-school samples from only one province, the small sample size which may affect representation and dynamics, self-reported data, and the lack of students' perspectives which in turn affect generalizability. Furthermore, the non-specificity of the branches of SMIE as not indicating the dynamics was another limitation. It is recommended that future research on this subject matter be done over larger areas and different institutions involving more stakeholders and using either longitudinal or mixed methods.